2013
DOI: 10.1371/journal.pone.0063716
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Staphylococcus aureus Nasal Colonization among Women and Men in a General Population

Abstract: BackgroundObesity and diabetes mellitus (DM) have been linked to increased risk of infections, and Staphylococcus aureus nasal colonization is a major risk factor for developing infections with the microbe. We therefore sought to find whether body mass index (BMI) and waist circumference (WC) could be associated with S. aureus colonization independent of DM.Methodology S. aureus colonization was assessed by nasal swab cultures among 2,169 women and 1,709 men, aged 30–87 years, in the population-based Tromsø St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 42 publications
5
39
1
Order By: Relevance
“…This result corroborates the finding obtained by Olsen et al (2013) for older men (aged 30-87). Furthermore, males who had a high frequency of respiratory infections also had higher BMI's than those with a low frequency of these diseases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result corroborates the finding obtained by Olsen et al (2013) for older men (aged 30-87). Furthermore, males who had a high frequency of respiratory infections also had higher BMI's than those with a low frequency of these diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Since we did not study persistent pathogen carriage (it was tested only once and not repeated after some time), it is possible that some of our subjects were only intermittent carriers. Studies by Olsen et al (2013) who collected also a second nasal swab after a median time of 28 days, however, showed that only 3.9% of participants had results that differed from the first swab nasal test. It is then unlikely that our results with only one swab are unreliable.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regardless of the mechanism, the susceptibility of mice with T2D to nasal colonization by S. aureus was increased. Clinical studies have indicated that both T2D and obesity increase the rate of S. aureus colonization in the nares (29,30). Thus, the T2D mouse simulates the human disease state.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to lean controls, obese women have a greater risk of S. aureus colonization (Olsen et al 2013), and obese patients have a greater risk of infection after surgical procedures. Obese psoriatic patients are more likely to develop severe psoriatic outbreaks that are difficult to treat.…”
Section: Adipocytes In Cutaneous Diseasementioning
confidence: 99%